Slovenian Journal of Public Health: The Journey so Far and the Road Ahead - FARKAŠ LAINŠČAK Jerneja; ŠVAB Igor (Slovenian Journal of Public Health)
The Slovenian Journal of Public Health, established 63 years ago as the official publication of the National Institute of Public Health in Slovenia, was initially aimed at tracking the development of public health in Slovenia and disseminating scientific advancements to professionals in the field. In 2000, a new editorial board took over and shifted the journal’s focus towards enhancing scientific rigour and achieving international recognition. This strategic transformation led to the journal being indexed in the Social Sciences Citation Index (SSCI) in 2009, specifically within the category of Public, Environmental & Occupational Health. The indexing enabled the journal to acquire its first impact factor in 2011, which has demonstrated a consistent upward trajectory, currently standing at 1.6 (IF2023). The journal has recently ascended to the third quartile of its field and is now recognised as the second highest-ranked medical journal in Slovenia. Following over two decades of successful leadership, the journal is poised to enter a new phase under an incoming editor-in-chief. It is imperative for the journal to sustain its contributions to public health by promoting high-quality scientific publications and facilitating critical discourse among researchers.